SYZYGIUM CUMINI (L.) SKEELS LEAF EXTRACT FRACTIONS AS ARGINASE INHIBITORS AND THE EFFECTS OF TANNINS ON THEIR ACTIVITY - HIDAYATI, ARI ARIEFAH; ELYA, BERNA; SAURIASARI, RANI (International Journal of Applied Pharmaceutics, 2020)
Objective: Arginase inhibition could be a potential therapeutic approach for endothelial dysfunction. Syzygium cumini (L.) Skeels leaves contain phenolic acids and flavonoids, which have been predicted to exhibit arginase inhibitory activity. Moreover, these leaves contain tannins, which can form complexes with enzymes and lead to false-positive results during biological testing. Therefore, this study was conducted to evaluate the arginase inhibitory activity of S. cumini leaf extract and fractions as well as to elucidate the effects of tannins on this activity. Methods: S. cumini leaves were fractionated using n-hexane, ethyl acetate, and methanol. A colorimetric method was employed to evaluate arginase inhibitory activity. Tannin elimination was performed through the gelatin precipitation method. Total phenolic and flavonoid contents of the fractions were calculated using the Folin–Ciocalteu and aluminum chloride methods, respectively. Results: Ethyl acetate and methanol fractions showed arginase inhibitory activity with half-maximal inhibitory concentrations (IC50) of 46.96 and 15.35 μg/mL, respectively. The methanol fraction was positive for tannins. After tannin elimination, this fraction exhibited less potent arginase inhibitory activity, with an IC50 value of 53.03 μg/mL. The ethyl acetate fraction showed higher total phenolic and flavonoid contents than the methanol fraction. Conclusion: Tannins affected the arginase inhibitory activity of the methanol fraction of S. cumini leaves; however, the ethyl acetate fraction did not contain tannins and could inhibit arginase activity.